DYNAMIC EVOLVEMENT ASSESSMENT AND FORECAST OF LAND USE BASED ON GEOGRAPHIC INFORMATION SYSTEM - Dongjie Guan; Xiaosong Lin; Weijun Gao; Weici Su; Kazunori Hokao (International Association of Lowland Technology, 2014)
Based on the land use patterns in the years of 1990, 1995, 2000 and 2005 acquired with the spatial technology of geographic information system (GIS), this study takes Kitakyushu city in Japan as a case to analyze and forecast the dynamic change and transformation of various land use types. Firstly, we use the spatial distribution maps to describe the changes of area and spatial distribution of land use in the past 15 years, and then the dynamic change models are established to evaluate the changes of speed and intensity of land use. The results indicate that each land use type has changed remarkably as the urbanization, and that the land use intensity has been transferring from extensive type to intensive type. Finally, we develop a transfer matrix of Markov to track the mutual transformation processes among the land use types, and to forecast the change tendency of future land use. The forecasting results reveal that the urban land will keep increasing at a decelerated speed, and it will be a long process for land use intensity to reach to the urbanization level.